Assessment of information content in visual signal: analysis of optical flow fractal complexity. Issue 3 (15th March 2016) - Malaia, Evie; Borneman, Joshua D.; Wilbur, Ronnie B.
ABSTRACT: We make a first attempt at distinguishing an information-carrying visual signal by comparing visual characteristics of American Sign Language to everyday human motion, to identify what clues might be available in one but not in the other. The comparison indicated significantly higher fractal complexity in sign language across tested frequency bands (0.01–15 Hz), as compared to everyday motion. A comparison of our results with other work showing high fractal complexity in the speech signal allows us to suggest the underlying properties of linguistic signals which allow babies to "tune into" a specific channel, or modality, during language acquisition.